New data on the bush-cricket Montana medvedevi (Orthoptera: Tettigoniidae), critically endangered in Europe (EU 28), and a comparison of its song with all known song patterns within the genus - Ivković, Slobodan; Iorgu, Ionuț Ștefan; Horvat, Laslo; Chobanov, Dragan; Korsunovskaya, Olga; Heller, Klaus-Gerhard (Zootaxa, 2017)
Montana medvedevi is reported for the first time from Serbia. New information about the distribution, morphology and song of this species is discussed. The song of M. medvedevi is different from that of all other members of the genus, all figured for comparison. Montana is quite diverse regarding the amplitude pattern of the calling song of its members (known in 15 species). Surprisingly, some Montana species seem to have two song patterns, one produced during the day and one at night.